2016
DOI: 10.1108/intr-11-2014-0299
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of social media on employee work performance

Abstract: Purpose – The purpose of this paper is to investigate the influence of social media on employees’ work performance, as well as the underlying mechanism for how they create value at work. Design/methodology/approach – Based on media synchronicity and social capital theories, the authors propose that social media can foster employees’ social capital and subsequently facilitate knowledge transfer. Both social capital and knowledge transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
280
6
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(315 citation statements)
references
References 46 publications
20
280
6
9
Order By: Relevance
“…Incorporating social media into workplace is regarded as a two-edged sword [13]. On the positive side, social media use at work was found to foster social capital [20], promote knowledge transfer [4], improve sense of cultural belonging [21], and increase group effectiveness [7]. Although some studies have mentioned the negative side of social media use [7,21], few of them explicitly examined it in relation to job performance.…”
Section: Two-factor Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating social media into workplace is regarded as a two-edged sword [13]. On the positive side, social media use at work was found to foster social capital [20], promote knowledge transfer [4], improve sense of cultural belonging [21], and increase group effectiveness [7]. Although some studies have mentioned the negative side of social media use [7,21], few of them explicitly examined it in relation to job performance.…”
Section: Two-factor Theorymentioning
confidence: 99%
“…Extant research tends to investigate the mechanism of social media use by considering its positive outcomes, such as social capital [2], knowledge sharing [4], and job performance [5]. For instance, Moqbel, Nevo, and Kock [5] found that the intensity of social media use at work is positively related to job performance.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the studies of relationship the social media and knowledge transfer. One of research was found that the social media was facilitated the knowledge transfer and work performance (Cao, Guo, Vogel, & Zhang, 2016). In the other research, the social media technologies were allowing for the transfer of tacit and explicit knowledge (Murphy, 2013).…”
Section: Literatur Reviewmentioning
confidence: 99%
“…The Culture of organization was means the special values and characteristics in an organization (Schein E. H., 1985;Schein E. H., 2004). Today, the social media is a part of organizational culture for reach the performance of employee and corporate (Shaqiri, 2015;Baloh & Trkman, 2003;Anderson, 2012;Cao, Guo, Vogel, & Zhang, 2016;Trainor, Andzulis, Rapp, & Agnihotr, 2013).…”
Section: Literatur Reviewmentioning
confidence: 99%
See 1 more Smart Citation